2017
DOI: 10.12973/eurasia.2017.01045a
|View full text |Cite
|
Sign up to set email alerts
|

Do Chinese Exporters Still Need Learning Spillovers from Foreign MNEs?

Abstract: The study investigates learning spillovers from local firms as well as MNEs in China, and their indirect effects on other firms' exporting, paying particular attention to inter-and intra-industry spillovers. We develop a synthetic model based on the treatment of spillovers in economics, geography and international business, testing four different spillover effects, measured by export propensity and intensity of local Chinese firms associated with four types of export agglomeration. We find significant, positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…We found that size positively impacts the export performance of a firm, meaning that the bigger the firm, the better the export performance will be. Zhao et al (2017) concluded that the relationship between size and export performance was an inverted U shape, so, until a certain size, the firms would have an improvement in export performance, but this would cease and then the effect would be the opposite. According to the authors, this would happen when a large firm is not motivated to export or to increase their exportations due to the significant size of the domestic marked that they already serve.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We found that size positively impacts the export performance of a firm, meaning that the bigger the firm, the better the export performance will be. Zhao et al (2017) concluded that the relationship between size and export performance was an inverted U shape, so, until a certain size, the firms would have an improvement in export performance, but this would cease and then the effect would be the opposite. According to the authors, this would happen when a large firm is not motivated to export or to increase their exportations due to the significant size of the domestic marked that they already serve.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the studies that analyze Chinese firms, these encompass samples from the same period and analyze the same agglomeration economy -local export spillovers. The measure of export performance is also the same -export propensity -with the exception of Zhao et al (2017) which also uses export intensity. The conclusions, even though similar regarding the impact as a whole, are different in regard to the firm's specific characteristics.…”
Section: The Role Of Agglomeration Economies On Export Performancementioning
confidence: 99%
See 2 more Smart Citations